Effectiveness of Implementing E-Books on Phase Equilibrium Based on Multiple Representations to Improve Students' Critical Thinking Skills - Wilda Syahri; Yusnaidar Yusnaidar; Muhaimin; Firdiawan Ekaputra (Postgraduate, University of Mataram, 2026)
This study aims to test the effectiveness of using e-books on phase equilibrium based on multiple representations in improving students’ critical thinking skills. The study design is non-randomized because subjects were not randomly assigned to the experimental and control groups. Both groups were given different treatments to observe the intervention’s effect on critical thinking skills. The experimental group received instruction using an e-book based on multiple representations, while the control group used conventional learning media, namely printed textbooks. The sample used in this study consisted of students enrolled in the Physical Chemistry II course in the Chemistry Education program at the Universitas Jambi, with Class B serving as the experimental group and Class A as the control group. The instrument used in this study was a critical thinking skills test designed to measure students’ critical thinking abilities, both before and after the implementation of the multiple-representation-based e-book. The results of the hypothesis test using ANCOVA yielded a significance value of 0.00, which is less than 0.05. Based on the research results, it can be concluded that the implementation of a multiple-representation-based e-book on phase equilibrium significantly improves students’ critical thinking skills.